Susceptibility of eggs of Idaea inquinata (Scop.) (Lepidoptera, Geometridae) to high and low temperatures. (January 2015) - Limonta, Lidia; Locatelli, Daria P.
Abstract: This study was carried out to determine the influence of low and high temperatures, at two relative humidities, on eggs of Idaea inquinata, and the time required to obtain complete mortality. Groups of one hundred eggs, 24–48 h old, not acclimatized, were kept at 7 or 12 ± 1 °C, with 35 or 70% r.h., for 5, 10, 13, 15, 16, 20, and 22 days, and at 40 ± 1 °C, 35 or 70% r.h., for 10, 13, 18, 22, 24 and 30 h. A test was also conducted at 50 ± 1 °C with 35 or 70% r.h. for 1 h. At the end of the exposure periods, eggs were transferred to 26 ± 1 °C and 70 ± 5% r.h. and checked daily. As control, hatching was observed on groups of one hundred eggs kept at 26 ± 1 °C and 70 ± 5% r.h. Experiments were replicated four times. The egg incubation period and the number of I . inquinata eggs hatched were not influenced by humidity. At 7 and 12 °C, twenty-two days were required to inhibit eggs hatching at both humidities. At 40 °C, egg hatching was inhibited after 38 h at 35% r.h., and after 40 h at 70% r.h. At 50 °C hatching was inhibited after 1 h at both 35 and 70% r.h. Highlights: We investigated the effect of low and high temperatures on eggs of Idaea inquinata at two relative humidities. The estimated LT95 for 24–48 h eggs was 18 days at 7 °C and 20 days at 12 °C. To obtain 95% mortality at 40 °C, a 26-h exposure was required; all eggs died after 1 h at 50 °C. Relative humidity did not influence egg mortality.